Pengaruh Karakteristik Perusahaan Dan Karakteristik Auditor Terhadap Audit Report Lag - Susanto, Androni; Tang, Sukiantono; haryanti, Rizka (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This research aims to analyze share price movements on the Indonesia Stock Exchange from 2018 to Abstract- The purpose of this writing is to examine and analyze the factors that influence auditor efficiency in completing the audit process which is proxied by audit report lag. The factors used in this research were selected by looking at company characteristics and auditor characteristics. Design/methodology/approach, company characteristics are proxied by Board Independence, financial condition, and profitability, while auditor characteristics are proxied by auditor reputation. The population of this research is all companies listed on the Indonesia Stock Exchange in 2018-2022. Based on the purposive sampling method, the number of samples obtained from 231 companies. Findings, ehe research results show that partially the financial condition variable has a significant negative effect on audit report lag. Meanwhile, the auditor reputation variable shows a significant influence on audit report lag.